Migration, capital formation, and house prices - Volker Grossmann; Andreas Schäfer; Thomas M. Steger (Institute for the Study of Labor (IZA), 2013)
We investigate the effects of interregional labor market integration in a two-sector, overlapping-generations model with land-intensive production in the non-tradable goods sector (housing). To capture the response to migration on housing supply, capital formation is endogenous, assuming that firms face capital adjustment costs. Our analysis highlights heterogeneous welfare effects of labor market integration. Whereas individuals without residential property lose from immigration due to increased housing costs, landowners may win. Moreover, we show how the relationship between migration and capital formation depends on initial conditions at the time of labor market integration. Our model is also capable to explain the reversal of migration during the transition to the steady state, like observed in East Germany after unification in 1990. It is also consistent with a gradually rising migration stock and house prices in high-productivity countries like Switzerland.
Keywords: D90; F20; O10; 330; capital formation; house prices; land distribution; migration; welfare